Illusions of Clustering: A Systematic Evaluation on the Effects of Clusters on Regional Economic Performance in Korea. (March 2022) - Shin, Hyunha; Hwang, Junseok
Korea has pursued a cluster-based policy to increase industrial competitiveness and to alleviate development gaps between the regions. However, local governments have often oversupplied clusters without an objective examination of the demands and conditions in the regions. Based on these concerns, this study analyses effects and interdependencies of factors related to regional innovation and growth in Korea. Employing a PCA method and a GLS regression models on panel data, we generated three composite factors, social, capacity, and clustering, and estimated their effects on regional economic performance. The results show that it is important to have a favorable socio-economic setting to foster growth by clusters. In addition, cluster-based policies may have weaker effects than expected, because the effect of R&D capacity on regional growth was stronger and longer lasting. Finally, some specific elements that most affected economic growth in Korea's regions are identified. The overall results indicate favorable environments should be established beforehand to foster regional growth with clusters, which confirms "jobs follow people."